Naturalization in Sports from the Perspective of Sports Nationalism Based on Bhinneka Tunggal Ika - Prasetio, Dicky Eko (Bhinneka Tunggal Ika: Pancasila Jurnal Internasional Berbahasa Indonesia, 2025)
Naturalization in sports is a global phenomenon that occurs worldwide, including in Indonesia. In Indonesia, this creates problems in the form of the stigma of "foreign players" or naturalized players versus local players, which causes issues, particularly in relation to the value of Bhinneka Tunggal Ika (Unity in Diversity). This research aims to analyze the aspects of naturalization in the field of sports as an effort to enhance national values, particularly Bhinneka Tunggal Ika, based on sports nationalism, while reaffirming reconstruction efforts in the legal field. This research is legal research that emphasizes the socio-legal aspects, using a conceptual and legislative approach. The research findings confirm that from a sports nationalism perspective, sports holds very positive values for strengthening national identity in society. The presence of naturalized players in the national team actually broadens the definition of nationality, so that society no longer sees citizenship solely as something born from blood ties and homeland, but also as an inclusive social bond that values the diversity of athletes' origins. Legal reconstruction to uphold the value of Bhinneka Tunggal Ika requires a revision of the Citizenship Law. This revision must emphasize the principle of priority in naturalization, giving primary opportunity to Indonesian descendants abroad or individuals with historical, cultural, or emotional ties to Indonesia as their ancestral country. The revision of the Citizenship Law must also regulate the substantive requirements that athletes undergoing the naturalization process must meet, including the obligation to participate in guidance and training that focuses on introducing and internalizing national insights, Pancasila values, the spirit of Bhinneka Tunggal Ika, and local wisdom, which are the cultural foundations of the Indonesian nation.